Frequency of intestinal parasitosis and its relationship with socio-sanitary conditions in children with ages between 1 and 7 years of the sector la pocaterra, Venezuela. (Revista Venezolana de Salud Pública, 2018)
The objective of the research was to determine the frequency of intestinal parasitosis in children from 1 to 7 years old, according to their socio-sanitary conditions, in a population located in the Municipality of Tocuyito, Urbanización La Pocaterra. The information on the socio-sanitary conditions was obtained through a questionnaire type survey (Annex 1), to characterize these conditions were taken into account criteria for measuring the condition of life of the Inter-American Institute for Social Development.
Keywords: intestinal parasitosis; conditions partner-toilets